An exact approach for the location routing problem with multiple routes - Macedo, Rita (2011)
We address a variant of the location routing problem where vehicles can perform several routes in the same planning period. This problem represents a combination of two problems, a vehicle routing problem, which determines the optimal set of routes to fulfill the demands of a set of customers, and a location problem, as the depots from which the vehicles performing the routes can be associated must be chosen from a set of possible locations. We explore a new pseudo-polynomial network flow model, whose nodes represent time instants, and whose arcs represent feasible vehicle routes. At the end of the paper, we report on a set of computational experiments conducted on instances adapted from the literature.